Analisis Stres Kerja Aparatur Sipil Negara dalam Pencapaian Tujuan Organisasi Pemerintah Daerah di Sumatera Barat - Rindu Wahyuni; Ivo Aprijona Simarmata; Yudika Bako; Boni Saputra; M. Fachri Adnan (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
The increasing demands of public services, bureaucratic complexity, high workloads, and digital transformation place growing pressure on Civil State Apparatus (ASN), potentially causing work stress that affects performance, service quality, and local government organizational goals. This study analyzes work stress among ASN, its impact on organizational goal achievement, and the role of leadership and organizational environment in reducing it in West Sumatra, using a literature review of academic publications from 2020-2026 with descriptive and thematic synthesis analysis. Results reveal that ASN work stress stems from excessive workload, role ambiguity, work conflict, bureaucratic changes, and organizational conditions, negatively impacting mental health, productivity, service quality, and organizational effectiveness. Conversely, supportive leadership, positive organizational culture, conducive work environment, motivation, and job satisfaction effectively reduce stress levels. These findings affirm that work stress management must become a strategic priority in public sector human resource management to optimize ASN performance and local government goal achievement.